A simulation-based Genetic Algorithm approach for refilling process with Clip Type Passive Manipulator - Che, HongLei; Wu, ZongZhi; Kang, RongXue; Yun, Chao; Jin, Hui (International Conference on Intelligent Systems Design and Applications, 2015)
A new Clip Type Passive Manipulator, instead of the Scissors Type Manipulator, is studied and applied for solving the problem of small capacity of the manipulator. When the capacity of the manipulator increases, the picking algorithm is considered for refilling process. The sequence of medicine storages is arranged in accordance with the picking algorithm, which is one important operational efficiency index of Fast Medicine Dispensing System (FMDS) in Pharmacy. Genetic Algorithm (GA) is used in the picking algorithm to search a better picking route. Based on the experiments and data analysis, results show the picking route value simulated-based GA by the Clip Type Manipulator more than 17% compared with the Scissors Type Manipulator. By increasing of picking points, the rate of optimization decreases firstly and then increases.